Review of the LEED Category in Materials and Resources for Developing Countries - Gurgun, Asli Pelin; Komurlu, Ruveyda; Arditi, David (ELSEVIER SCIENCE BV, 2015)
Material selection in sustainable projects affects the environment a great deal. Selected materials gain importance as they can contaminate the environment and can produce waste during construction. Use of limited resources has also environmental impacts. Thus, considering sustainable materials in the projects and appropriate consumption of available resources are important for sustainability considerations. The danger of running out of resources and the consequences of contamination of the habitat point out to the importance of green building certification systems. Issues such as storage and collection of recyclables, waste management planning, PBT source reduction, sourcing of raw materials, material ingredients, and design for flexibility that are treated in this category are difficult to implement in developing countries, mainly because they are based on local practices. The use of materials and resources accounts approximately for 11% of the points a building can receive for LEED v4 certification. However, the use of LEED in countries other than the U.S. can be controversial as local conditions are effective in earning credentials required for certification. This study aims to review the materials and resources category of LEED. Comparison of local practices in selected developing countries is made based on credits in this category to provide guidelines for green projects in those countries. It is expected that practitioners in developing countries will benefit from the outcome of this study. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Sustainability; LEED; Developing countries; Sustainable materials; ENERGY; Science & Technology - Other Topics; Engineering